Effects of molybdenum on nutrition, quality, and flavour compounds of strawberry (Fragaria×ananassa Duch. cv. Akihime) fruit - Li LIU; Wei XIAO; Mei-ling JI; Chao YANG; Ling LI; Dong-sheng GAO; Xi-ling FU (Journal of Integrative Agriculture, 2017)
Molybdenum (Mo) is an essential trace element in plant nutrition and physiology. It affects photosynthesis and photosynthate accumulation, therefore also affecting fruit quality and nutritional content. This study assessed the effects of different sodium molybdate (Na2MoO4) concentrations on strawberry. Five different Mo concentrations were applied in this experiment, including 0, 67.5, 135, 168.75, 202.5 g ha−1, respectively. The mineral concentration, including nitrogen (N), Mo, iron (Fe), copper (Cu), and selenium (Se) was assessed in strawberry fruit, as well as chlorophyll content, nutrition quality, taste and aroma. Results showed that net photosynthetic rate (Pn) and chlorophyll content for the strawberry plants increased with an increase in Mo concentration; and the contents of N, Mo, Fe, Cu, total soluble solids (TSS), titratable acidity (TA), sweetness, some sugars, organic acids, and some volatile compounds in the fruit all increased, as well. However, the Mo concentration did not significantly affect the concentrations of Se, sucrose, lactic acid, acetic acid, and some aroma compounds. Fruit sprayed with 135 g ha−1 Mo exhibited the highest TSS and sweetness values, as well as the highest N and Fe concentrations among all the treatments. Pn value and chlorophyll content, fructose, glucose, sorbitol and total sugar contents in fruit supplied with 135 g ha−1 Mo were also higher than that in other treatments. Fruit sprayed with a Mo concentration of 67.5 g ha−1 exhibited significantly higher ascorbic acid (AsA) values than that of control. Ninety-seven volatile compounds were identified in fruit extracted by head-space solid-phase microextraction (HS-SPME) coupled with gas chromatography-mass spectrometry (GC-MS). Fruits sprayed with 135 g ha−1 Mo had the highest concentrations of six characteristic aroma compounds, including methyl butanoate, γ-decalactone, ethyl butanoate, methyl hexanoate, γ-dodecalactone, and ethyl caproate.